Health care needs of older people living permanently in a residential home setting in Gauteng - MM Chabeli (AOSIS, 2003)
This article reviews some of the prevailing health needs of elderly people living permanently in a residential old age home. A qualitative, exploratory and descriptive design was employed. Twenty-one black elderly people were purposively selected to participate in a focus group interview session for the purpose of describing their perception of their health care needs. From descriptive content analysis, three main data sets emerged, namely physical health needs, unmet psychological needs and the need for a healthy social relationship. Recommendations to deal with these health needs were made based on the empirical data supported by literature. Measures of trustworthiness were ensured as described by Lincoln and Guba (1985:316-327).